Biochemical and molecular characterizations of cypermethrin resistance in laboratory-selected cypermethrin-resistant strains of Tetranychus urticae Koch. (Acari: Tetranychidae). Issue 6 (18th August 2018) - Çağatay, Naciye Sena; Riga, Maria; Vontas, John; Çevik, Bayram; Ay, Recep
ABSTRACT: Pyrethroids are commonly used pesticides for controlling agricultural pests. A pyrethroid resistant strain of T. urticae was obtained after laboratory selection with cypermethrin for determining mechanisms of cypermethrin resistance. TaqMan diagnostic assay as well as sequencing of voltage gated sodium channel (VGSC) gene were performed in order to detect previously known mutations in German susceptible strain (GSS) confirming that it does not carry any of the known VGSC mutations. Therefore, GSS strain was selected with cypermethrin and the resistant C6 strain was generated that is free of VGSC mutations. Toxicity assay data revealed relatively high resistance levels of the C6 strain (54.24-folds) in comparison to GSS. All inhibitors (piperonyl butoxide (PBO), esterases, P450; S-benzyl-O, O-diisopropylphosphorothioate (IBP), esterases; and diethyl maleate (DEM), glutathione S-transferase (GST)) were used in combined toxicity assays against the major detoxification enzymes, synergized resistance by 1.41-, 1.61-, and 2.27-fold, respectively. In the C6 strain, activities of P450, GST, and esterase showed elevated activity in comparison to GSS. By application of TaqMan diagnostic assay, we confirmed that both GSS and C6 T. urticae strains are free of VGSC mutations, indicating that detoxification-based cypermethrin resistance mechanisms are involved in resistance and have significant effect on the phenotype.